2016
DOI: 10.1177/0271678x15625578
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic penumbra as a trigger for intracranial pressure rise – A potential cause for collateral failure and infarct progression?

Abstract: We have recently shown that intracranial pressure (ICP) increases dramatically 24 h after minor intraluminal thread occlusion with reperfusion, independent of edema. Some of the largest ICP rises were observed in rats with the smallest final infarcts. A possible alternate mechanism for this ICP rise is an increase of cerebrospinal fluid (CSF) volume secondary to choroid plexus damage (a known complication of the intraluminal stroke model used). Alternatively, submaximal injury may be needed to induce ICP eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…MCAo, a striatal stroke model, reduces blood ow to the choroid plexus by around 62% and causes choroidal oedema leading to reduced blood-CSF barrier integrity and increased CSF secretion [20]. Further, the earlier time point of our investigation may explain the smaller ICP rise, as we would expect ICP to continue to rise and peak at 22 hours post-stroke as previously observed [19]. We chose this time point to observe any changes that may contribute to ICP rise as we expect changes to reduce later as the system returns to normal.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…MCAo, a striatal stroke model, reduces blood ow to the choroid plexus by around 62% and causes choroidal oedema leading to reduced blood-CSF barrier integrity and increased CSF secretion [20]. Further, the earlier time point of our investigation may explain the smaller ICP rise, as we would expect ICP to continue to rise and peak at 22 hours post-stroke as previously observed [19]. We chose this time point to observe any changes that may contribute to ICP rise as we expect changes to reduce later as the system returns to normal.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, 6 out of 12 stroke animals had ICP rise 18 hours post-stroke. This ICP rise was smaller than we previously reported with MCAo at 24 hours and photothrombotic stroke at 22 to 24 hours post-stroke [8,9,19]. Here, we used a photothrombotic technique to produce a cortical ischaemia instead of a striatal ischaemia.…”
Section: Discussionmentioning
confidence: 76%
“…Other authors have suggested that a rise in intracranial pressure (ICP) can cause a collapse in the collateral circulation29 and in animal models ICP rise of even 5 mm Hg can cause significantly retarded flow via collateral pathways. This change in the flow seems to be related to as of yet unidentified cellular processes within the ischaemic penumbra as they are oedema-independent 30. Other proposed mechanisms are cerebral venous steal,31 reversed Robin Hood syndrome32 and blood pressure fluctuations secondary to autonomic dysfunction33 as well as others 34.…”
Section: Discussionmentioning
confidence: 93%
“…While ICP was not monitored in our study, dynamic difference in ICP may occur during acute between aged and young rats and may contribute to accelerated collateral failure observed here. Notably, Beard et al [75][76][77] stated that changes in collateral flow poststroke appear to be primarily driven by the pressure drop across the collateral vessel, and were not due to changes in vessel diameter. That is, as ICP increases, cerebral perfusion pressure is reduced and collateral flow declines, providing a possible explanation for collateral failure.…”
Section: Discussionmentioning
confidence: 99%